2020
DOI: 10.1093/nar/gkaa667
|View full text |Cite
|
Sign up to set email alerts
|

Structural, biochemical and functional analyses of tRNA-monooxygenase enzyme MiaE from Pseudomonas putida provide insights into tRNA/MiaE interaction

Abstract: MiaE (2-methylthio-N6-isopentenyl-adenosine37-tRNA monooxygenase) is a unique non-heme diiron enzyme that catalyzes the O2-dependent post-transcriptional allylic hydroxylation of a hypermodified nucleotide 2-methylthio-N6-isopentenyl-adenosine (ms2i6A37) at position 37 of selected tRNA molecules to produce 2-methylthio-N6–4-hydroxyisopentenyl-adenosine (ms2io6A37). Here, we report the in vivo activity, biochemical, spectroscopic characterization and X-ray crystal structure of MiaE from Pseudomonas putida. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Yet, trans -selective hydroxylation of tRNA-bound iPR or 2MeSiPR by the same enzyme was reported by others [ 62 , 63 ]. The origin of zeatins in the tRNA of some organisms is entirely unclear, as the presence of the miaE gene is reportedly limited to a few bacterial genera [ 64 ]; however, up-to-date results of BLASTp searches (not shown) using MiaE from Pseudomonas putida [ 65 ] as a query suggests the far wider distribution of MiaE among bacteria than previously anticipated.…”
Section: Formation Of Trans -Zeatin: Unclarified Pathwaysmentioning
confidence: 99%
“…Yet, trans -selective hydroxylation of tRNA-bound iPR or 2MeSiPR by the same enzyme was reported by others [ 62 , 63 ]. The origin of zeatins in the tRNA of some organisms is entirely unclear, as the presence of the miaE gene is reportedly limited to a few bacterial genera [ 64 ]; however, up-to-date results of BLASTp searches (not shown) using MiaE from Pseudomonas putida [ 65 ] as a query suggests the far wider distribution of MiaE among bacteria than previously anticipated.…”
Section: Formation Of Trans -Zeatin: Unclarified Pathwaysmentioning
confidence: 99%
“…S4) were collected on beamline MASSIF-3 under cryogenic conditions. Integration and refinement statistics (Table 1) show that this crystal diffracted at relatively high resolution (d = 1.59 A ˚), and thus, the refined structure (PDB entry 8afj) reveals a level of detail that can be fairly compared with the aerobic structure of MiaE previously deposited (PDB entry 6zmb; Carpentier et al, 2020). The anoxic reduced diiron centre structure in the 2F o À F c map at the 2 level is depicted in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…The enzyme Pp-MiaE from P. putida is a redox monooxygenase that catalyses the post-transcriptional hydroxylation of adenosine nucleotides at position 37 of selected tRNAs (Mathevon et al, 2007). Previous crystallographic studies revealed that the structure of the enzyme in the oxidized resting state consists of a four -helix bundle housing a diiron catalytic centre typical of the non-heme diiron monooxygenase family (Carpentier et al, 2020). For this test, we used an alternative crystallization condition of Pp-MiaE, producing two crystalline forms in large quantity, long needle-shaped and diamond-shaped crystals, which are both easy to manage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations